Unsettling Native Art Histories on the Northwest Coast - Jonaitis, Aldona; Bunn-Marcuse, Kathryn (Book collections on Project MUSE., 2020)
Inseparable from its communities, Northwest Coast art functions aesthetically and performatively beyond the scope of non-Indigenous scholarship, from demonstrating kinship connections to manifesting spiritual power. Contributors to this volume foreground Indigenous understandings in recognition of this rich context and its historical erasure within the discipline of art history.0By centering voices that uphold Indigenous priorities, integrating the expertise of Indigenous knowledge holders about their artistic heritage, and questioning current institutional practices, these new essays "unsettle" Northwest Coast art studies. Key themes include discussions of cultural heritage protections and Native sovereignty; re-centering women and their critical role in transmitting cultural knowledge; reflecting on decolonization work in museums; and examining how artworks function as living documents. The volume exemplifies respectful and relational engagement with Indigenous art and advocates for more accountable scholarship and practices.